PSXV-12 The effect of condensed tannin-containing diets on lipogenic genes expression in meat goats: A Pilot Study. (7th December 2018) - Min, B; Mienaltowski, M; Wang, H; Terrill, T; Gurung, N
Abstract: The objective of this study was to determine whether the condensed tannin (CT)-containing sericea lespedeza pellet (SLP; 13.6% CT), ground pine bark (PB; 16.3% CT), or its combination (SLP+PB) would have any effects on lipogeneic gene expression in meat goats. 24 Kiko-crossbreed goats (BW = 38.6 ± 2.7 kg) were randomly assigned to one of the 4 treats. (n = 6/treat.): 1) 30% bermudagrass hay and 70% grain mix, 2) 30% PB and 70% grain mix, 3) 30% SLP and 70% grain mix, and 4) 15% PB, 15% SLP, and 70% grain mix. All goats were slaughtered at the end of the study (d 42) and liver samples were collected and frozen at −80°C. Total RNA was extracted using QIAGEN according to manufacturer's instructions. Data were processed by the Kal's Z test. For identified fatty acids (FA) lipogenesis-related genes were selected including sterol regulatory element binding factor, nuclear receptor sub-family, fatty acids synthase, Acyl CoA carboxylase, stearol-coenzyme A desaturase, pyruvate kinase, glucokinase, and peroxisome proliferator-activated receptor. Feeding both CT-containing diets has no effect on Gck, Gckr, Nr1h, Pklr, and Srebf genes. However, feeding the PB diet affected negative (down regulated) responses, including Acadl (-106; long chain FA), Acadsb (-43; short chain FA), Acadvl (-5.1; long chain), and Acaca (-1.5), or positive expression (up regulated) of Acad (155), Acadm (107.6), and Pparg (17) compared to control diet. Goats fed the SLP diet affected both negative responses, including Acadm(-3.9), Acadsb (-5.5), and Pparg (-35), or positively impacted Acadl (44.9), Acadvl (13.3) Acaca (1.8), and Fasn (1.12) compared to control. Feeding PB and SLP mixed diets also showed intermediate responses in goat gene expression. Data suggested that CT-containing diets strongly affected on both Acac and Pparg genes that can provides the malonyl-CoA for the biosynthesis of FA (Acac).